Pengaruh Pelayanan Aparat Kelurahan Terhadap Kepuasan Masyarakat - Tiara Ningsi Putri Maaruf; Irwan Yantu; Melizubaida Mahmud; Meyko Panigoro; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The research aimed to figure out the effect of village apparatus service on community satisfaction in Tapa Village, Sipatana Subdistrict. This research employed a quantitative approach with a survey research method. The data used were primary data obtained from distributing questionnaires to the community of Tapa Village, Sipatana Subdistric, with a sample of 40 respondents. In the meantime, the data analysis technique used simple linear regression. The research finding denoted that there was an effect of village apparatus service on community satisfaction in Tapa Village, Sipatana Subdistrict. The effect of the village apparatus service on community satisfaction was 71,4 while the remaining 28,6% was affected by variables that were not examined in this research